Empowerment of the healthy living community movement (Germas) through training on making traditional beverages in Tonja Village, Denpasar - Arianty, A.A.Ayu Arun Suwi; Wirawan, Putu Eka; Susanti, Luh Eka; Sudiarta, I Nyoman; Arnawa, I Gusti Suka (Community Empowerment)
Current economic condition is not an ideal phase due to the Covid 19 Pandemic. The impact is felt by all aspects of society, including the society of Tonja village who mostly work in the hospitality and tourism business. The International Tourism and Business Institute seeks to contribute to family economic defense. The purpose of the community service is providing knowledge and training to the community about making traditional beverage that are beneficial for body health and creating innovative products that have the opportunity to be produced commercially by the community in the healthy living community movement. The method of implementation is by conducting workshops and demonstrations. The results obtained have a positive effect for the PKK in Tonja Village to continue to innovate during the pandemic by creating innovative products.